(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Neurodisability is an umbrella term for conditions associated with impairment involving the nervous system. The parents of these children remain worried about the cause of the disability and seek the diagnosis. Nowadays radiological diagnosis by CT scan is possible in most of the cases which may help in the management of such children. Objective: To correlate between clinical and CT scan findings in neurodisabled children. Materials and Methods: One hundred children with neurodisability were selected randomly who were scanned by 6, 16 and 128 slice CT scanners. This retrospective study was conducted in CMH Dhaka and Central Hospital Limited, Dhaka in between 2010 to 2014. Results: Abnormal CT scan was found in 57 cases out of 100 patients having neurodisability. A large number of patients having neurodisability are suffering from psychomotor delay, motor delay, seizure disorder and speech difficulty. Hypoxic ischaemic injury in perinatal period is one of the major causes of the disability. Conclusion: CT scan is very effective to find out the cause of neurodisability in less time (around 25 to 30 seconds) and is widely available in Bangladesh. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 93-97